Specialized photoreceptor composition in the raptor fovea. Issue 9 (13th March 2017) - Mitkus, Mindaugas; Olsson, Peter; Toomey, Matthew B.; Corbo, Joseph C.; Kelber, Almut
Abstract: The retinae of many bird species contain a depression with high photoreceptor density known as the fovea. Many species of raptors have two foveae, a deep central fovea and a shallower temporal fovea. Birds have six types of photoreceptors: rods, active in dim light, double cones that are thought to mediate achromatic discrimination, and four types of single cones mediating color vision. To maximize visual acuity, the fovea should only contain photoreceptors contributing to high‐resolution vision. Interestingly, it has been suggested that raptors might lack double cones in the fovea. We used transmission electron microscopy and immunohistochemistry to evaluate this claim in five raptor species: the common buzzard ( Buteo buteo ), the honey buzzard ( Pernis apivorus ), the Eurasian sparrowhawk ( Accipiter nisus ), the red kite ( Milvus milvus ), and the peregrine falcon ( Falco peregrinus ). We found that all species, except the Eurasian sparrowhawk, lack double cones in the center of the central fovea. The size of the double cone‐free zone differed between species. Only the common buzzard had a double cone‐free zone in the temporal fovea. In three species, we examined opsin expression in the central fovea and found evidence that rod opsin positive cells were absent and violet‐sensitive cone and green‐sensitive cone opsin positive cells were present. We conclude that not only double cones, but also single cones may contribute to high‐resolution vision in birds, and that raptors may in fact possess high‐resolution tetrachromatic vision in the central fovea. Abstract : Using transmission electron microscopy and immunohistochemistry we confirmed earlier indications that raptor foveae can be rod and double cone‐free. Most likely, not only double cones but also single cones contribute to achromatic high‐resolution vision in birds, in general.